Assessment of Financial Performance of Siti Fatimah Hospital, South Sumatra Province, In The Application of The Regional Public Service Agency (PPK-Blud) Financial Management Pattern - Djaky Nanda Parita; Mohamad Adam; Mu’izzuddin Mu’izzuddin (Publikasi Indonesia, 2024)
Regional General Hospital (RSUD) is a Government-Owned Hospital tasked with providing health services for the community. The purpose of this study is to measure the financial performance of the Siti Fatimah Regional General Hospital (RSUD) of South Sumatra Province; since 2018, it has become a Regional Public Service Agency (BLUD). Data collection techniques are carried out by interview, observation and documentation methods. The data analysis method uses Financial Ratios and BLU Financial Management Compliance by the Regulation of the Director General of Treasury Number PER-22 / PB / 2020. The results of this study, from 2018 to 2022, when viewed from Financial Ratios, show that several ratios have not received optimal scores. Several indicators have not received an optimal score from the BLU Financial Management Compliance level. When viewed as a whole from the assessment of financial aspect performance, Siti Fatimah Hospital of South Sumatra Province has received a GOOD predicate. However, it has not achieved the most optimal score.